Conoce a MEMO, el chatbot que transforma cómo medimos la dieta en Guatemala - Ramos Solorzano, Gresia Dalal; Lizarazo Torres, Miguel Angel; Arce Gomez, Daniela; Jimenez Rodas, Daniel Ricardo (2026)
In Guatemala, the use of digital tools such as WhatsApp offers an effective opportunity to collect timely information on diet quality at the community level. In this context, an informational video was developed about the MEMO chatbot, designed to support individuals receiving the Diet Quality Questionnaire (DQQ) survey and to strengthen their confidence to participate. In 2024, distrust related to potential fraud was identified as a key barrier to response rates; therefore, the video clearly explains the purpose of the initiative, presents partner organizations, and details data protection measures, thereby encouraging participation. This approach has enabled the generation of faster and more accessible data, reduced operational costs, and strengthened informed decision-making to improve diet quality and promote healthier and more resilient communities.